A contour error definition, estimation approach and control structure for six-dimensional robotic machining tasks. (February 2022) - Zhao, Huan; Li, Xiangfei; Ge, Kedi; Ding, Han
Highlights: A contour error definition, estimation approach and control structure for the 6D robotic machining tasks are proposed. The definition of robotic contour error in the 6D machining is intuitive, and provides the prerequisite for the estimation and control of the robotic contour error. The contour error estimation approach is locally iterative, and depends only on the reference pose information and has high accuracy and high efficiency. The contouring control structure is designed by compensating the contour error components to the velocity commands in the robotic task space, which is simple and effective. Abstract: Robots are increasingly employed in machining applications, such as milling, grinding and polishing, etc, and contour error can be used to assess the robotic machining accuracy quantitatively. For the robotic machining tasks, such as the grinding of complex surface parts, the reduction of contour error needs to consider the six dimensions of the robotic task space. However, at present, there is no suitable research work directly related to the contour error definition and estimation for the six-dimensional (6D) robotic machining tasks, and the corresponding control structure is rarely involved. For resolving the above problems, this article presents a contour error definition, estimation approach and control structure for the 6D robotic machining tasks. To be specific, the definition of robotic contour error in the 6D machining is first introduced. Then, based on the bidirectional search, Fibonacci search and spherical linear interpolation algorithms, a locally iterative robotic contour error estimation approach with high accuracy and high efficiency is provided. Finally, by compensating the weighted contour error components to the velocity commands in the robotic task space, a simple as well as effective components-based contouring control structure is designed. The real experiments are performed on a six-degrees-of-freedom robot. The results reveal that the definition of robotic contour error given is intuitive, and the discrepancies between the position and orientation contour error estimates and the corresponding true values are very small within 0.01062 µm and 0.8959 µrad, respectively. The designed contouring control structure can reduce effectively the contour errors, and compared with the tracking control only, the mean position and orientation contour errors are reduced by about 30% and 28%, respectively.